Valve repair in patients with infective endocarditis. (25th November 2020) - Scheggi, V; Olivotto, I; Alterini, B; Merilli, I; Starnazzi, F; Ceschia, N; Andrei, V; Stefano, P.L
Abstract: Background: Valve repair is considered the treatment of choice for native mitral and tricuspid valve regurgitation but the rate of feasibility when the defect is caused by acute infective endocarditis (IE) is debated. We report the experience of valve repair versus replacement following IE in a high-volume surgical center. Methods: We retrospectively analyzed 351 consecutive patients (123 women) admitted to our department with definite diagnosis of IE. IE occurred on native valves in 219 patients (62%) and on prosthetic valves in 132 (38%). Among native valves, IE involved the aortic valve in 105 cases (48%), mitral valve in 97 cases (44%) and tricuspid valve in 17 (8%). Since only native mitral and tricuspid valves are elegible for surgical repair, we limited the analysis to this subset (114 patients); of them, 92 (80.7%) underwent surgery (the final cohort) and 22 were treated conservatively, 13 due to absence of surgical indication and 9 due to prohibitive surgical risk. Long-term follow-up was obtained by structured telephone interviews. Primary endpoints were mortality and freedom from recurrent endocarditis. Secondary endpoints were the postoperative incidence of major adverse events (hospitalization for any cause, pace-maker implantation, new onset of atrial fibrillation, sternal dehiscence). Results: Mean age at surgery was 61.9 years (SD 14.5). Mean vegetation length was 11.6 mm (SD 8.8). Endocarditis was left-sided in 80 (87%). Among the 92 surgical patients, 58 (63%) underwent valve replacement and 34 valve repair (37%). Mortality was similar between valve repair and replacement (15 vs 12%). Adverse events rate (19% vs 16%) and relapse were not statistically different between repair and replacement procedures. Conclusions: The present study shows that a sizeable subgroup of consecutive patients with native mitral or tricuspid IE are amenable to valve repair in expert hands. Outcome of repair in IE is comparable to valve replacement mid-term, and should be considered whenever possible, as in degenerative valve disease. Funding Acknowledgement: Type of funding source: None